Evaluation of bone marrow reticulin in patients with chronic immune thrombocytopenia treated with eltrombopag: Data from the EXTEND study. Issue 7 (July 2015) - Brynes, Russell K.; Orazi, Attilio; Theodore, Dickens; Burgess, Paul; Bailey, Christine K.; Thein, Maung M.; Bakshi, Kalpana K.
<x xml:space="preserve">Abstract</x> Thrombopoietin receptor agonists, which raise platelet counts in patients with chronic immune thrombocytopenia, may be associated with increases in bone marrow (BM) reticulin. Patients with chronic immune thrombocytopenia participating in the Eltrombopag Extended Dosing (EXTEND) study underwent BM biopsies to identify clinically relevant BM fibrosis‐related increases. Specimens were centrally reviewed by 2 hematopathologists. Two hundred thirty‐two biopsy specimens were collected from 117 patients treated for ≤5.5 years. Moderate to marked reticulin fibrosis was found in 2 patients. After withdrawing from the study, the biopsy of 1 patient reverted to normal. There were no other pathologic changes identified among on‐treatment specimens, and no pattern of abnormal reticulin deposition associated with eltrombopag treatment was evident. Am. J. Hematol. 90:598–601, 2015. © 2015 Wiley Periodicals, Inc.